Plavanie v XXI veke: prognozy i perspektivy - Bulgakova, N. Z.; Popov, O. I.; Partyka, L. I. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
Actual developments in training, performance developments and changes in body composition and other parameters in swimming are analysed. From this, strategies for the preparation of national teams are drawn.